Instalación del sistema de alcantarillado sanitario en la localidad de Pinto Recodo - Padilla Maldonado, Joel (2006)
The present project of thesis denominated "INSTALLATION Of the SYSTEM OF SANITARY SEWAGE SYSTEM IN the LOCALITY OF PINTO RECODO" arises before the urgent necessity of the population of the Locality Pinto Recodo's locality to solve the multiple problems originated by the deficiency of this service of basic cleaning, for this reason the present work aims to remedy these problems with a technical project that consists in the evaluation of the domestic remainders through the implementation of a system of sanitary sewage system and the respective treatment of residual waters. Also, the present Project is framed within the specific objective to improve the quality of the services through increasing the access to the services with the implementation of the• Network of Water-drainage and Plant of corresponding Treatment, with the purpose of preserving and of guaranteeing the sustainability of the health of the population and the ecosystem. In the design of the System of Sanitary Sewage system of the Locality of Pinto Recodo, 1 consider myself in the first place in the sequence of its development, the data collection, such which they were obtained directly through surveys, information of the institutions of the locality and the check and information of other studies, and mainly by means of multiple works of field. The data collection embraced four important aspects: those that allowed to fix the magnitude of the deficiency or necessity of the system (rates of morbidity, child mortality, served area and served population); those that allowed to appreciate the magnitude of the system (present population, future population, volumes and periods of design); the data corresponding to the characteristics of the .zone (topography, geology, cadastre, type of ground, vulnerability, environmental impact, climate, water obstacles, areas available and location of the elements of the system) and finally the complementary data (capacity of payment of the population, minimum wage, number of connections of existing water and existing construction eq uipments). Secondly, after the data collection, it was come to its ordering, analysis and processing by means of pictures, formulas and graphs, establishing in parallel form the identification of problems that will include the system and the planning of the posible solutions. In the data processing, one resorted to the aid of comparative tables on parameters, Norms and the National Regulation of Constructions. Once raised the optima! alternative it was come to the analysis of all the technical and economic aspects that take part in this alternative of solution, obtaining of the necessary documentation, detailed analyses, calculations and presizing of the elements of the system. After the previous thing it was come to the detailed sizing from the elements of the system, elaboration of planes, metrados, budgets, chronograms, and all the final details. For a better development the structure of the Thesis Project has been divided in VIII chapters distributed of the following way: in the CHAPTER 1 appears the general lntroduction of the project, the situational trame considering all the necessary aspects for an optima! diagnose fit to the present reality of the zone in study, this information will allow us to make a guessed right analysis for the later definition and selection of the advisable alternative but for the projected system; in the CHAPTER 11 detail all the theoretical fundamentación on which all the parameters of the design are based; in the CHAPTER 111 consider the materials and methods like tools of the elaboration of the present document specifying the technical criteria in the respective designs of ali the sanitary infrastructure; in the CHAPTER IV detail to the obtained results of the studies results and severa! designs; in the CHAPTER V discuss the results obtained in previous chapter; the CHAPTER VI contains the conclusions obtained after ali the analysis and process of the elaboration of the present project later to propase respective recommendations; the CHAPTER VII contemplate the bibliographical references and finally in the CHAPTER VIII annexed the complementary information, special studies themselves, economic and social criteria that a technical study of this nature requires.